Customer Integration, Top Management Support, Organizational Structure and Supply Chain Technology Adoption. Examining the Mediating Role of Intention to Adopt Specific Supply Chain Technologya - Marlina Widiyanti; Marsudi Lestariningsih; Iin Irwanto; Endang Sulistya Rini (International Journal of Supply Chain Management, 2020)
The main focus of the present study is to examine the impact of top management support, organizational structure, and customer integration on the intention to adopt specific technology management and adoption of e-supply chain technology. Additionally, mediating impact of intention to specific technology between top management support, organizational structure, customer integration and adoption of new technology is assessed as well. The data is collected from the employees of commercial banks of Indonesia. The data collection technique adopted was stratified random sampling. The collected data was analyzed through PLS-SEM using PLS 3.2.1. The findings of the study revealed that all of the proposed direct as well, and mediating hypothesis is accepted. The findings of the study are important for the practitioners of the banking sector to adopt strategy by which they can adopt new technology. Moreover, this study fills the gap of limited studies related to technology in the supply chain perspective of the banking sector.